Co-Production in Poverty Reduction: The Case of PAGBAG-O, a Non-Government Organization in Negros Oriental - Credo, Jan Antoni A. (Silliman Journal, 2023)
Civil society organizations in the Philippines have largely proven themselves to be dependable partners of the government in service delivery, especially in areas of governance where gaps in public service delivery are well-pronounced. Where the government has fallen short of its mandate, civil society organizations, more popularly known as the Third Sector, within the context of co-production, work with the public sector to address these deficiencies. In the province of Negros Oriental, the Panaghugpong sa mga Gagmayng Bayanihang Grupo sa Oriental Negros, Inc. (PAGBAG-O, Inc.) - a federation of small farmers, fisherfolks, and women’s cooperative and IPs organizations in the province, has been at the forefront of coproduction to improve public service delivery to marginalized groups. This paper explores the poverty-alleviating potential of PAGBAG-O through improved public service delivery to end users-consumers through the lens of co-production.